Particle size distribution and clay minerals in dryland soils of Aceh Besar, Indonesia. Issue 1 (November 2021) - Sufardi, S; Arabia, T; Khairullah, K; Apriani, I
Abstract: Soil particle size distribution is a fundamental physical property affecting other soil properties. This research aims to determine the distribution of soil particles and the composition of clay minerals on each layer of the horizon in four soil profiles (P1, P2, P3, and P4) with different parent materials in the dryland of Aceh Besar district which includes Entisols Jantho, Andisols Saree, Inceptisols Cucum, and Oxisols Lembah Seulawah. Particle size distribution (or texture) and bulk density (BD) were analyzed in the laboratory. Soil structure and consistency were observed directly in the field. The type of clay minerals was identified by X-ray diffraction, while Fe, Al, and Si-oxide were extracted by dithionite-citrate solution. The results shown that the particle size distribution and the physical properties of dryland soils of Aceh Besar vary between soil orders. Andisols Saree has better physical properties than the physical properties of other soils and low bulk density. The Al, Fe, and Si fractions and clay mineral composition in the soil profiles also vary considerably between soil orders. The Andisols are dominated by allophane minerals (amorphous fractions) while Entisols, Inceptisols and Oxisols consist of mixed minerals of feldspar, quartz, halloysite, goethite, and other clay minerals. These soil orders have some soil physical constraints i.e. high soil bulk density, low water holding capacity and poor soil structures. Improvements in the physical properties of the soil on Aceh Besar dryland are indispensable to improve the quality of the soil.